A New Strategy toward "Simple" Water‐Soluble AIE Probes for Hypoxia Detection. (19th June 2019) - Xu, Changhuo; Zou, Hang; Zhao, Zheng; Zhang, Pengfei; Kwok, Ryan T. K.; Lam, Jacky W. Y.; Sung, Herman H. Y.; Williams, Ian D.; Tang, Ben Zhong
Abstract: Hypoxia‐responsive fluorescent probes have emerged as a novel scaffold for tumor diagnosis. However, dilemma often exists between simple synthesis and high water solubility in traditional probes. Owing to the intrinsic property of N‐oxides, herein, a new strategy is proposed to design and synthesize probes for in vitro hypoxia imaging. Equipped with tetraphenylethene (TPE), the N‐oxides exhibit aggregation‐induced emission characteristics and emit no light in aqueous solutions. Interestingly, the N‐oxides can be reduced by ferrous ions in different rates. The aggregation of the resulting hydrophobic TPE residues restricts the intramolecular motions of the molecules, which "turns‐on" their fluorescence. The NO covalent bond of one molecule can be specifically cleaved by cellular reductase overexpressed under hypoxic conditions, and thus turn‐on hypoxia imaging in vitro is achieved. The new strategy to design hypoxia imaging probes is extremely valuable and has great potential for application in tumor diagnosis. Abstract : By combining the aggregation‐induced emission (AIE)‐active tetraphenylethene group with zwitterionic N‐oxide functionality, a new strategy to design and synthesize water‐soluble AIE luminogens yet with simple chemistry is presented for hypoxia imaging. This approach subtly resolves the contradiction between simple synthesis and excellent water solubility in traditional hypoxia‐triggered probes.